KELUARGA BERENCANA DALAM PERSPEKTIF HADIS: MENYELAMI PETUNJUK NABI TERKAIT KESEIMBANGAN HIDUP - Hafizoh, Nurul; Muhid (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study examines the concept of family planning in the perspective of hadith with the aim of understanding the Prophet Muhammad's instructions related to the balance of life which includes spiritual, social, and economic dimensions. The focus of this research is on analyzing the hadith-reports relevant to the practice of family planning, including birth control, planning the number of children, and holistic family welfare. A qualitative-descriptive approach was used to explore the hadith texts and the historical and social contexts in which they were uttered in order to understand the Prophet's guidance in its entirety. The results show that the Prophet Muhammad provided flexible and contextualized guidance on family planning. In various traditions, there are indications of support for family planning when it is aimed at ensuring the well-being of the individual, family and society. The Prophet also emphasized the importance of moral and social responsibility in determining the number of children, taking into account factors such as economic capacity, maternal health, and family stability. This study highlights that Islamic teachings are dynamic and capable of responding to contemporary challenges, including the issue of family planning. A holistic understanding of these traditions can support the implementation of family planning programs that are in line with Islamic values, without neglecting health, economic and social aspects. As such, this study contributes to modern Islamic literature, particularly in the context of applying religious principles to support the balance of life and the welfare of society.